2012
DOI: 10.1111/nph.12066
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of foliar endophytes to quantitative resistance to Melampsora rust

Abstract: SummaryFoliar endophytes of Populus do not induce the hypersensitive response associated with major genes for resistance to Melampsora leaf rust. But they could contribute to the quantitative resistance that represents a second line of defense. Quantitative resistance is thought to be determined by suites of minor genes in both host and pathogen that are influenced by the abiotic environment. Here, we determined the relative importance to quantitative resistance of foliar endophytes, one element of the biotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 30 publications
2
69
3
1
Order By: Relevance
“…Quantitative resistance does not completely prevent infection, but rather involves many genes working together to reduce pathogen latent period, infection efficiency and/or spore production (Geiger and Heun 1989). Raghavendra and Newcombe (2013) found that different endophytes reduced rust locally (i.e., not systemically) by varying degrees (0.6 to 16 times). Overall, variation among endophyteinoculated and control leaves explained 54% of the observed variation in rust symptom severity, whereas host genotype explained only 5.0%, and host genotype-by-endophyte interaction only 1% (i.e., the endophytes were consistently ranked in the magnitude of their effects across genotypes).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantitative resistance does not completely prevent infection, but rather involves many genes working together to reduce pathogen latent period, infection efficiency and/or spore production (Geiger and Heun 1989). Raghavendra and Newcombe (2013) found that different endophytes reduced rust locally (i.e., not systemically) by varying degrees (0.6 to 16 times). Overall, variation among endophyteinoculated and control leaves explained 54% of the observed variation in rust symptom severity, whereas host genotype explained only 5.0%, and host genotype-by-endophyte interaction only 1% (i.e., the endophytes were consistently ranked in the magnitude of their effects across genotypes).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, endophyte effects almost completely swamped plant genotypic effects on pathogens, leading to the hypothesis that endophytes are a second line of pathogen defense in plants-after major genes for resistance (Flor 1955), but before quantitative genetic resistance (Raghavendra and Newcombe 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, neither nematode species has been reported to cause damage to plants. The presence of fungal-feeding nematodes undoubtedly affects the balance of endophytic fungi within a leaf community, and incidence of disease can depend as much or more on composition of endophyte species than on plant genotype (Raghavendra and Newcombe, 2013). Furthermore, the ability of an Aphelenchoides species to cause plant disease may depend on the composition of different endophytic fungi within a given host.…”
Section: Discussionmentioning
confidence: 99%